2016
DOI: 10.3748/wjg.v22.i13.3621
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a computed tomography classification for hepatic alveolar echinococcosis

Abstract: The proposed CT-morphological classification (EMUC-CT) is intended to facilitate the recognition and interpretation of lesions in hepatic alveolar echinococcosis. This could help to interpret different clinical courses better and shall assist in the context of scientific studies to improve the comparability of CT findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 22 publications
2
77
0
12
Order By: Relevance
“…Nevertheless, no integrative typing system has been established so far, and they were asymmetric when de ning clinical stage or lesion activity regarding different lesion types. Besides, among the lesion types that proposed by Kodama et al, Kratzer et al and Graeter et al, there were not clear integrative bridge to de nitely link them, and no relevant study which used all these imaging tools in same patient cohort has been reported [18][19][20]. And this was why we chose to reclassify lesions based on two factors (calci cation and necrosis).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, no integrative typing system has been established so far, and they were asymmetric when de ning clinical stage or lesion activity regarding different lesion types. Besides, among the lesion types that proposed by Kodama et al, Kratzer et al and Graeter et al, there were not clear integrative bridge to de nitely link them, and no relevant study which used all these imaging tools in same patient cohort has been reported [18][19][20]. And this was why we chose to reclassify lesions based on two factors (calci cation and necrosis).…”
Section: Discussionmentioning
confidence: 98%
“…In the past, several imaging tools demonstrated lesion types for hepatic AE [18][19][20]. And there were some other imaging methods and researches on comparison of different imaging tools [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…And there were some other imaging methods and researches on comparison of different imaging tools [21][22][23][24][25]. These no relevant study which used all these imaging tools in same patient cohort has been reported [18][19][20]. And this was why we chose to reclassify lesions based on two factors (calcification and necrosis).…”
Section: Discussionmentioning
confidence: 99%
“…However, imaging in alveolar echinococcosis has seen major developments in recent years. Recently, a first CT‐based classification (EMUC‐CT; Echinococcosis Multilocularis Ulm Classification ‐ CT) and an ultrasound classification for lesions of alveolar echinococcosis have been published to facilitate comparability, but it remains to be seen whether it is also informative for the clinical course of the disease. Dual‐energy CT may allow to examine the vascularity of hepatic lesions of alveolar echinococcosis and awaits evaluation as a tool to assess the risk of progression .…”
Section: Discussionmentioning
confidence: 99%